The Correlation Between Knowledge, Attitudes, and Reproductive Health Behavior Among Junior High School Students in Batam City - Silvia Mona; Ana Faizah (Yayasan Media Utama Sains, 2025)
Background: Adolescence is a transitional period characterised by significant physical, psychological, and social changes, including reproductive maturation. Limited knowledge and negative attitudes toward reproductive health can increase adolescents’ risk of engaging in unhealthy behaviours. Understanding their knowledge, attitudes, and behaviours is crucial for developing effective educational interventions. Objective: This study examined the relationships among knowledge, attitudes, and reproductive health behaviours among adolescents. Method: A quantitative, cross-sectional study was conducted at a junior high school in Batam City from March to June 2024. Of 250 students, 72 were selected using the Slovin formula and simple random sampling. Data were collected through a structured questionnaire and analysed using univariate and bivariate methods, including the Chi-square test. Results: Most respondents had moderate knowledge of reproductive health (41.7%), positive attitudes (63.9%), and good reproductive health behaviour (55.6%). Bivariate analysis showed significant correlations between knowledge and behaviour (p = 0.021) and between attitudes and behaviour (p = 0.015). Conclusion: Knowledge and attitudes are significantly associated with adolescents’ reproductive health behaviour. Strengthening reproductive health education in schools is recommended to improve adolescents’ knowledge, attitudes, and practices.